Unraveling the Therapeutic Potential of Apigenin: Targeting CDK6 in Cancer Treatment - Alothaid, Hani (Indian Journal of Pharmaceutical Education and Research)
Background: The pursuit of effective cancer therapies hinges upon the identification and characterization of molecular targets amenable to precise modulation. Herein, we present a comprehensive investigation into the potential of Apigenin as a therapeutic agent targeting Cyclin-Dependent Kinase 6 (CDK6), a critical regulator of cell cycle progression implicated in tumorigenesis. Materials and Methods: Initially, we employed protein structure homology modelling to elucidate the high-resolution structure of CDK6, revealing a model of exceptional quality with a GMQE score of 0.87 and a QMEANDisCo Global score of 0.96±0.05. Subsequent cavity detection analysis unveiled five prominent cavities within CDK6, with Cavity 1 (C1) exhibiting remarkable size and volume, thus warranting further exploration through molecular docking studies. Molecular docking simulations identified. Results: Apigenin as the most promising inhibitor of CDK6, demonstrating a strong binding affinity with the target protein. This interaction was validated through redocking, which consistently reaffirmed the robust binding between Apigenin and CDK6. Furthermore, ADMET predictions and SwissTargetPrediction confirmed Apigenin's drug-like properties and its potential to target CDK6 inhibition. Functional assays revealed Apigenin's concentration-dependent cytotoxic effects on HCT-15 (colorectal cancer), HeLa-229 (cervical adenocarcinoma), and PC-3 (prostatic adenocarcinoma) cancer cell lines, accompanied by a significant reduction in CDK6 mRNA expression (p<0.001) and kinase activity (p<0.01). Conclusion: Collectively, these findings underscore Apigenin's potential as a therapeutic candidate for targeting CDK6 in cancer treatment, warranting for further preclinical and clinical investigations.
Keywords: Apigenin; Cancer; Cyclin-Dependent Kinase 6 (CDK6); HCT-15 cancer cells; HeLa-229 cancer cells; PC-3 cancer cells; targeted therapy.